An event study of home and host country patent generation in Chinese MNEs undertaking strategic asset acquisitions in developed markets. Issue 5 (October 2015) - Anderson, John; Sutherland, Dylan; Severe, Sean
Highlights We model the impact of Chinese strategic-asset related acquisitions on innovation. Such acquisitions do not impact innovation in acquired developed market firms. Domestic innovation in the Chinese parents, however, does improve. One explanation is Chinese MNEs deploy acquired strategic-assets domestically. Asset-seeking may therefore be strongly motivated by domestic market considerations.